2023
DOI: 10.3390/foods12081644
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Delicacy: Variation in Quality and Sensory Aspects in Wild Boar (Sus scrofa) Meat and Comparison to Pork Meat—A Case Study

Abstract: The aim of this study was to evaluate quality and sensory variation in wild boar meat in comparison to pork. Meat quality in wild boar is expected to vary more compared to pork due to different feeding environment, age and gender. In order to be able to promote wild boar meat as a sustainable high-quality product, there is a need to evaluate the variation in meat quality attributes, including technological, compositional and sensory/texture aspects. We evaluated carcass characteristics, pH, colour, lipid profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The nutritional and biological value of wild boar meat has certain advantages, compared to domestic pork. Sampels et al (2023) showed that the content of muscle fat in wild pigs was 4.5-5.2%, compared to 2.9% in domestic pigs. On the other hand, Żmijewski and Korzeniowski (2001) reported a lower mass fraction of fat and a high protein content in the meat of wild boars slaughtered in Poland.…”
Section: Introductionmentioning
confidence: 98%
“…The nutritional and biological value of wild boar meat has certain advantages, compared to domestic pork. Sampels et al (2023) showed that the content of muscle fat in wild pigs was 4.5-5.2%, compared to 2.9% in domestic pigs. On the other hand, Żmijewski and Korzeniowski (2001) reported a lower mass fraction of fat and a high protein content in the meat of wild boars slaughtered in Poland.…”
Section: Introductionmentioning
confidence: 98%